A Critique on the Book “Poets and Poetry” - Sayyed Reza Mirahmadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The irreplaceable role of literary historians in proving literary events as well as highlighting the role of writers is undeniable. If it cannot be considered the best tool, it can be considered at least one of the bests in expressing and showing the unique role of literature in the construction and social context and cultural development of society.  One of the most prolific and insightful works of the talented and insightful writer, Mostafa Shaka'a, is the book “Poetry and Poets in the Abbasi Era” which seems to be very influential and practical due to the author’s critical style. Having skimmed the book, what seemed to be very interesting is that the book's possible shortcomings are outweighed by its strengths. One of the best results of this study is that Shaka'a has played an effective role, by mastering the poetry and poets of this very important period of literature and very deep critique, as well as charting the literary style of some poets who appeared in other similar books, who were showed either very dull no significant in other books. The chapters are also based on this approach of the author and his balances on this approach, also reflect his surrounding knowledge and insight. Perhaps most of his weaknesses have been in forms, and sometimes in concept, such as accusing Abu Nawas of nationalism, which, of course, does not detract from the book’s strengths.